Non-invasive electrophysiological monitoring vs conventional monitoring during labour in a tertiary obstetric care centre in the Netherlands: study protocol of a cohort intervention random sampling study (NIEM-II study) - S G Oei; P B Q Berben; N D de Klerk; M van der Ven; A F Fransen; H J Niemarkt; E R van den Heuvel; M B van der Hout-van der Jagt; J O E H van Laar (BMJ Open)
Introduction Conventional cardiotocography (CTG) has been used extensively to monitor the fetal condition during labour. However, conventional non-invasive monitoring is limited by the difficulty of obtaining an adequate signal quality, particularly in the case of obese parturients. Furthermore, the rate of operative deliveries keeps rising despite the ability for conventional intrapartum monitoring. Electrophysiological monitoring is an alternative technique that has been developed over the past decades to improve signal quality. This non-invasive, transabdominal and wireless alternative measures fetal heart rate by fetal electrocardiography (NI-fECG), and uterine activity by electrohysterography (EHG). Both NI-fECG and EHG have been proven to be more accurate and reliable than conventional non-invasive methods and are less affected by maternal Body Mass Index. Nevertheless, it is still unknown whether electrophysiological intrapartum monitoring leads to better obstetric and neonatal outcomes. This study aims to investigate whether electrophysiological monitoring during labour affects the number of operative interventions compared with conventional monitoring during labour.Methods and analysis This is a single-centre cohort intervention random sampling study which will be performed in a tertiary obstetric care centre. In total, 3471 term pregnant women with a singleton fetus in cephalic position and indication for continuous fetal monitoring during labour will be included. Eligible women will be prospectively included in the cohort for conventional monitoring. From these women, 90.9% of women will be randomly sampled and will be offered electrophysiological monitoring. A historical cohort of an additional 2100 women who received conventional monitoring will be added to the conventional group. This historical cohort was collected between April 2019 and February 2023. The primary outcome will be the number of operative interventions during labour. Secondary outcome measures include maternal and neonatal outcomes, patient and healthcare professional perspectives and costs.Ethics and dissemination This study received approval from the Medical Ethics Committee of Máxima Medical Centre (W22.071) on 1 November 2023. All participants will provide informed consent prior to data collection. Results of the study will be disseminated in peer-reviewed scientific journals and conference presentations.Trial registration number NCT06135961.